A Structural Atlas of the Developing Zebrafish Telencephalon Based on Spatially-Restricted Transgene Expression - Turner, Katherine J.; Hawkins, Thomas A.; Henriques, Pedro M.; Valdivia, Leonardo E.; Bianco, Isaac H.; Wilson, Stephen W.; Folgueira, Mónica (Frontiers in Neuroanatomy, 2022)
Zebrafish telencephalon acquires an everted morphology by a two-step process that occurs from 1 to 5 days post-fertilization (dpf). Little is known about how this process affects the positioning of discrete telencephalic cell populations, hindering our understanding of how eversion impacts telencephalic structural organization. In this study, we characterize the neurochemistry, cycle state and morphology of an EGFP positive (+) cell population in the telencephalon of Et(gata2:EGFP)bi105 transgenic fish during eversion and up to 20dpf. We map the transgene insertion to the early-growth-response-gene-3 (egr3) locus and show that EGFP expression recapitulates endogenous egr3 expression throughout much of the pallial telencephalon. Using the gata2:EGFPbi105 transgene, in combination with other well-characterized transgenes and structural markers, we track the development of various cell populations in the zebrafish telencephalon as it undergoes the morphological changes underlying eversion. These datasets were registered to reference brains to form an atlas of telencephalic development at key stages of the eversion process (1dpf, 2dpf, and 5dpf) and compared to expression in adulthood. Finally, we registered gata2:EGFPbi105 expression to the Zebrafish Brain Browser 6dpf reference brain (ZBB, see Marquart et al., 2015, 2017; Tabor et al., 2019), to allow comparison of this expression pattern with anatomical data already in ZBB.